PCR Detection of Cyclic Lipodepsinonapeptide-Producing Pseudomonas syringae pv. syringae and Similarity of Strains - Sorensen, Kevin N. (American Society for Microbiology, 1998)
Many strains of Pseudomonas syringae pv. syringae produce one of four classes of small cyclic lipodepsinonapeptides: syringomycins, syringostatins, syringotoxins, or pseudomycins. These metabolites are phytotoxic and growth inhibitory against a broad spectrum of fungi. Their production is dependent upon the expression of conserved biosynthesis and export genes syrB and syrD, respectively. PCR and oligonucleotide primers specific for a 752-bp fragment of syrB were used to identify cyclic lipodepsinonapeptide-producing strains of P. syringae pv. syringae. In contrast, PCR amplification with primers based on syrD did not always correlate with possession of the syrD gene, as indicated by Southern blot analysis, or with cyclic lipodepsinonapeptide production. Sequence comparisons of 400 nucleotides from the syrB PCR-amplified fragments showed 94% plot similarity among 27 strains. In a sequence phenogram, syringostatin and syringotoxin producers were grouped apart from syringomycin-producing strain B301D, with sequences that differed by eight and nine conserved base substitutions, respectively. PCR amplification of the 752-bp syrB fragment offers rapid and accurate detection of cyclic lipodepsinonapeptide-producing strains, and its sequence provides some predictive capabilities for identifying syringotoxin and syringostatin producers.